Analisis Semiotika dalam Iklan Shopee 12.12 Birthday Sale Edisi Blackpink - Adinda Rita Dara; Muchlis Muchlis (Program Studi Ilmu Komunikasi Fakultas Dakwah dan Komunikasi, UIN Sunan Ampel Surabaya, 2019)
Meaning is a thought or reference that cannot be determined absolutely but is always in the relationship between symbol and reference. Meanwhile, image is a description of reality or perception that does not have to match what is described and must be different in every opinion. The focus of this research is how the meaning of the image of women is displayed in Shopee advertisements. This study uses Charles Sander Pierce's semiotic analysis technique with a critical approach. This technique is a way of looking at social reality that can occur in real life and can find out how to interpret women as objects in Shopee advertisements. From the results of this study, the researchers found that the image of women is described as attracting public interest to buy or use a product or service